DISCRETE TIME OR CONTINUOUS TIME, THAT IS THE QUESTION: THE CASE OF SAMUELSON’S MULTIPLIER-ACCELERATOR MODEL - LUO, Yinghao; LUO, Mingmin (Theoretical and Practical Research in Economic Fields, 2016)
A basic problem in economic dynamics is the choice of continuous-time or discrete-time in mathematical modeling. In this paper, we study the continuous-time Samuelson’s multiplier-accelerator model and compare this continuous-time model with its classical discrete-time model. We find that although time scales do not affect the probability of return to equilibrium solution in Samuelson’s multiplier-accelerator model, but time scales have an influence on the perfect symmetry of periodic motion.